All Days 2022
DOI: 10.56952/arma-2022-0969
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Interlaminar Difference on Height Propagation Behavior of Hydraulic Fracture in Lucaogou Shale

Abstract: The shale oil reservoir of Lucaogou Formation is characterized by complex lithology changes in vertical direction and lamination. To simulate the lithology variation of shale oil formation, downhole cores with different lithologies were prepared and bonded to layered samples. After that, the influence of interlaminar difference on propagation behavior of hydraulic fractures (HFs) was investigated through laboratory hydraulic fracturing and mechanical characteristics analysis. The result shows that mechanically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Deng et al [13] studied the influence of the original rock stress on the fracture behavior of a single fracture based on the stress intensity factor criterion, but did not consider the influence of the presence of natural fractures on fracture initiation and expansion. Zhang et al [14] analyzed the influence of displacement and stress difference on hydraulic fracturing fracture propagation by carrying out largescale true triaxial tests on shale outbursts containing natural fractures. Hou et al [15] carried out true triaxial hydraulic fracturing material model experiments on tight limestone outcroppings, and analyzed the influence of in situ stress difference, fracturing fluid viscosity, variable displacement, acid treatment and other factors on fracture propagation law.…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al [13] studied the influence of the original rock stress on the fracture behavior of a single fracture based on the stress intensity factor criterion, but did not consider the influence of the presence of natural fractures on fracture initiation and expansion. Zhang et al [14] analyzed the influence of displacement and stress difference on hydraulic fracturing fracture propagation by carrying out largescale true triaxial tests on shale outbursts containing natural fractures. Hou et al [15] carried out true triaxial hydraulic fracturing material model experiments on tight limestone outcroppings, and analyzed the influence of in situ stress difference, fracturing fluid viscosity, variable displacement, acid treatment and other factors on fracture propagation law.…”
Section: Introductionmentioning
confidence: 99%
“…This brings great difficulty to simulation of the reservoir. Therefore, it is fairly important to understand the mechanical and fracture properties of different layers, which is the key to optimizing a hydraulic fracturing strategy [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [6] analyzed the crack height and its ability to penetrate bedding under the influence of layer thickness and lithology based on a triaxial hydraulic fracturing simulation. Zhang et al [8] found that the bedding direction of a Lucaogou rock has a significant effect on its tensile strength and brittleness. Zou et al [11] believed that the difference in rock mechanics between layers cannot effectively inhibit the growth of fracture height but has a significant effect on the fracture width.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have studied the effects of natural fractures on the propagation pattern and fracture morphology of hydraulic fractures mainly by means of experiments and numerical simulations. Zhou et al 5,6 Cheng et al 7 and Zhang et al 8 studied the effects of main stress difference and natural fractures on the fracture morphology of horizontal wells by means of true triaxial hydraulic fracture experiments and acoustic emission monitoring, respectively. However, these studies did not elaborate the relationship and sensitivity between the influencing factors.…”
Section: Introductionmentioning
confidence: 99%